Innovation Capability Terhadap Kinerja Organisasi: Dynamic Marketing Capability Sebagai Variabel Mediasi - Muawanah, Cindy Choridatul; Pujianto, Wahyu Eko (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
This study aims to determine the effect of innovation capability and dynamic marketing capability on the performance of SME organizations in Tanggulangin District. This type of research is quantitative with an explanatory research approach. Data is analyzed using SmartPLS 4.0. The sampling method is accidental sampling with a sample size of 63 respondents who have been calculated using the Slovin formula. To ensure the data will not be done validity test and reliability test. Innovation capability has a positive effect on organizational performance, innovation capability has a positive effect on dynamic marketing capability, dynamic marketing capability has a negative effect on organizational performance, and dynamic marketing capability has a negative effect in mediating innovation capability on organizational performance in SMEs in Tanggulangin District.